Turning the Surface Electronic Effect Over Core‐Shell CoS2─FexCo1‐xS2 Nanooctahedra Toward Electrochemical Water Splitting in the Alkaline Medium - Lian‐Ming Lyu; Yu‐Chung Chang; Han‐Jung Li; Pei‐En Wang; Ruei‐Hung Juang; Ming‐Yen Lu; Cheng‐Shiuan Li; Chun‐Hong Kuo (Advanced Science)
Abstract The long‐term challenge in overall water splitting is the conflict in the pH condition of electrolytes for achieving efficient hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) at the same time, in addition to the typical cost issue in catalysts. It hence raises an intense research interest in seeking cost‐efficient non‐noble metal electrocatalysts as well as compromising electrolyte conditions for electrocatalytic HER and OER. To tackle the problems, various approaches are demonstrated to engineer the electronic effect on the active sites of catalysts for enhancing the activities. In this work, the core‐shell CoS2─FexCo1‐xS2 nanooctahedra is fabricated with a tunable Fe content over the surface and took them as the model catalyst for systematic studies in alkaline OER and HER. By various X‐ray spectroscopies as well as electron microscopy, the results showed that the shells of CoS2─FexCo1‐xS2 nanooctahedra formed the {111} surfaces of Fe0.9Co1.0S2 and Fe0.25Co0.75S2 with and without the promotion by OH− anions during the syntheses. Catalyzed by the CoS2, Fe0.25Co0.75S2, and Fe0.9Co1.0S2 {111} surfaces, the results of alkaline OER and HER indicated the Fe0.9Co1.0S2 the most superior activities by virtue of the optimized Fe─Co electronic effect. From the predictions by density functional theory (DFT) calculations in reaction thermodynamics, the energy barriers in OER and HER both follow the order of Fe0.9Co0.1S2(111) < Fe0.25Co0.75S2(111) < CoS2(111). However, FeS2(111) is worse than Fe0.9Co0.1S2(111). From the confirmations by in‐situ X‐ray spectroscopies in reaction kinetics, the Co sites of Fe0.9Co0.1S2(111) on the core‐shell nanooctahedra exhibited much higher activities than those of CoS2(111) under the applied potentials for OER and HER, which reflected the electronic benefits from the existing Fe neighbors.